Pengembangan Buku Pengayaan Perubahan Sosial sebagai Sumber Belajar Mata Pelajaran Ilmu Pengetahuan Sosial - Bambang Tejokusumo (Faculty of Education Universitas Negeri Malang, 2018)
Abstract: This research and development based on the purpose: (1) to produce enrichment book with contain is social change in Rembang Subdistrict Purbalingga Regency and using Junior High School student; and (2) to produce manual using for teacher take advantages enrichment book with contain is social change in Rembang Subdistrict Purbalingga Regency and using Junior High School student. This research is research and development with procedural model with descriptive adaptation from from Borg dan Gall (1983), with the steps as follows: (1) research and collection the first information; (2) planning; (3) the form movement of the first product; (4) first test; (5) product revision; (6) field test; (7) revision product; (8) field test; (9) the last product revision; and (10) dissemination and implementation. The research and development result that validation product by the content expert, language experts and graphic got score 90%, 84%, and 59%. Tryout this product by 5 social science teachers and 15 students from 3 different Junior High Schools with the average score 92,48 and 93,3; but there are some advices and responses from social science teachers and also the students for book revision. Abstrak: Penelitian dan pengembangan ini bertujuan untuk: (1) menghasilkan buku pengayaan perubahan sosial di Kecamatan Rembang Kabupaten Purbalingga Jawa Tengah sebagai sumber belajar siswa di SMP; dan (2) menghasilkan pedoman penggunaan bagi guru dalam memanfaatkan buku pengayaan perubahan sosial di Kecamatan Rembang Kabupaten Purbalingga Jawa Tengah sebagai sumber belajar siswa di SMP. Jenis Penelitian ini adalah penelitian pengembangan (Research and Development) dengan model prosedural yang bersifat deskriptif adaptasi dari Borg dan Gall (1983), dengan langkah-langkah: (1) penelitan dan pengumpulan informasi awal; (2) perencanaan; (3) pengembangan format produk awal; (4) uji coba awal; (5) revisi produk; (6) uji coba lapangan; (7) revisi produk; (8) uji lapangan; (9) revisi produk akhir; dan (10) deseminasi dan implementasi. Validasi produk dilakukan oleh ahli materi, ahli bahasa dan ahli grafika, dengan tingkat kevalidan masing-masing yaitu 90%, 84%, dan 59%. Uji coba produk dilakukan oleh 5 guru IPS SMP dan 15 siswa SMP memperoleh rata-rata skor 92,48 dan 93,3; namun juga mendapat tanggapan dan saran untuk perbaikan buku pengayaan ini.